2018
DOI: 10.1016/j.redox.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of tau improves mitochondrial function and cognitive abilities in the hippocampus

Abstract: Tau is a key protein for microtubule stability; however, post-translationally modified tau contributes to neurodegenerative diseases by forming tau aggregates in the neurons. Previous reports from our group and others have shown that pathological forms of tau are toxic and impair mitochondrial function, whereas tau deletion is neuroprotective. However, the effects of tau ablation on brain structure and function in young mice have not been fully elucidated. Therefore, the aim of this study was to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 104 publications
(138 reference statements)
1
79
0
Order By: Relevance
“…3F ). Interestingly, tau-null mice were also recently reported to perform better than WT littermates in a spatial navigation task (Ahmed et al, 2014) and showed enhanced exploration and recognition memory (Jara et al, 2018). Given these collective results, the effects of dTau loss on Drosophila PSD-LTM and the molecular targets offered by our comparative proteomic data, potential physiological roles for dTau in these processes are currently under investigation.…”
Section: Dtau Translation Regulation and Neuroplasticitymentioning
confidence: 68%
“…3F ). Interestingly, tau-null mice were also recently reported to perform better than WT littermates in a spatial navigation task (Ahmed et al, 2014) and showed enhanced exploration and recognition memory (Jara et al, 2018). Given these collective results, the effects of dTau loss on Drosophila PSD-LTM and the molecular targets offered by our comparative proteomic data, potential physiological roles for dTau in these processes are currently under investigation.…”
Section: Dtau Translation Regulation and Neuroplasticitymentioning
confidence: 68%
“…Second, the mitochondrial permeability transition pore (mPTP) opening is involved in cell death pathway in numerous diseases . Tau protein may play a role the mPTP opening because Tau ablation inhibited mPTP formation by reducing cyclophilin D protein, which improved mitochondrial bioenergetics in mouse hippocampal cells . Despite the role of TSPO in the modulation of the mPTP opening being questioned, there is some evidence indicating the blocking activity of new TSPO ligands against Aβ‐induced mPTP opening, thus promoting cell survival .…”
Section: Discussionmentioning
confidence: 99%
“…The development of tau pathology is a complex multifactorial process. Hyperphosphorylated tau in AD patients' brains causes configuration changes and the loss of tubulin polymerization capacity (60, 61), resulting in defective microtubule functioning (62).…”
Section: Tau Hyperphosphorylation Hypothesismentioning
confidence: 99%